PERANAN ROEHANA KUDUS 1911-1920 DI SUMATERA BARAT SEBAGAI SUMBER BELAJAR UNTUK MENUMBUHKAN SIKAP KEMANDIRIAN GENERASI MUDA - Qonita Fadhila (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2023)
This paper discusses the role and struggle of Roehana Kudus 1911-1920 in West Sumatra in empowering Koto Gadang women through education and economy so that they have independence. This effort was a way for women to fight gender inequality that occurred in West Sumatra at that time. Roehana Kudus' struggle is not limited to women in Koto Gadang, but through the Soenting Melajoe newspaper, Roehana spread her thoughts to reach women in various regions. The struggle of Roehana Kudus gave birth to the importance of the value of independence, so that this can be used as a source of learning for today's young generation to foster an attitude of independence. On that basis, the purpose of writing this study is to provide an overview and analyze the struggle and role of Roehana Kudus 1911-1920 in West Sumatra as a learning resource to foster an attitude of independence for the younger generation today. This research uses a qualitative research approach that produces data presented in the form of narrative descriptions and uses library research types.